Implementasi Model Guided Discovery Learning Dengan Pendekatan SETS Berbantuan E-Modul Kimia Terhadap Literasi Sains Peserta Didik SMAN 1 Padang - Yulia Asri Warlinda; Yerimadesi Yerimadesi; Hardeli Hardeli; Andromeda Andromeda (Jurnal Penelitian Pendidikan IPA, 2022)
Chemical concepts are not only taught abstractly by the teacher, but students also need to do it independently to better understand, of course, with the help of the teacher. So it is necessary to intervene in learning such as the right way in learning the right way. The purpose of this study was to demonstrate the effect of implementing a guided discovery learning model with the SETS approach with the help of a chemistry module on the scientific skills of SMA Negeri 1 Padang class XI students. The method of this study uses a quasi-experimental type of study, and the study design used is a randomized control group test-only design. The subject of this study is all students in class XI SMA Negeri 1 Padang, who are actively enrolled in 2021/202, which consists of seven classes. Groups of research populations are grouped using random sampling techniques. Multiple-choice test equipment/2-step literacy is based on up to 20 items. Technical analysis of data in this study is quantitative data analysis by testing hypotheses using the average analysis of the similarity test of 2 groups of unpaired samples (independent). The results of the hypothesis test, namely tcount> ttable, determined that the research hypothesis was accepted. This means that the implementation of a guided discovery learning model with the SETS approach supported by the Chemistry E module will have a significant impact on the scientific abilities of Class XI students in SMA Negeri 1 Padang